2015
DOI: 10.1038/jid.2015.318
|View full text |Cite
|
Sign up to set email alerts
|

TSLP Directly Interacts with Skin-Homing Th2 Cells Highly Expressing its Receptor to Enhance IL-4 Production in Atopic Dermatitis

Abstract: Thymic stromal lymphopoietin (TSLP) is overtly expressed on skin lesions of atopic dermatitis (AD), and the initiative role of TSLP-activated DCs in AD has gained much attention in the past few years, while its actions on other immune cells such as T cells have been given less notice. We aimed to clarify whether TSLP receptor (TSLPR) is expressed on certain populations of T cells and whether TSLP possesses the capability to directly interact with T cells from AD patients. Peripheral lymphocytes from 51 AD pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 23 publications
1
82
0
1
Order By: Relevance
“…4a,b). Since direct interactions between T cells and TSLP have recently been demonstrated 53 , we investigated the role of TSLP on T cell migration. Pre-incubation of T cells with a TSLP receptor antibody inhibited dermal infiltration, while direct application of recombinant human TSLP on the dermis equivalents or T cells cultured in transwells resulted in CD4 + T cell migration (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4a,b). Since direct interactions between T cells and TSLP have recently been demonstrated 53 , we investigated the role of TSLP on T cell migration. Pre-incubation of T cells with a TSLP receptor antibody inhibited dermal infiltration, while direct application of recombinant human TSLP on the dermis equivalents or T cells cultured in transwells resulted in CD4 + T cell migration (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although a low level of anti-SmCL3 antibody was detected following a challenge infection of vaccinated mice these were far lower than those observed for SmCB1, suggesting a more prominent infection-associated anamnestic response for the latter peptidase which is supported by it well-known immunogenicity in experimental and natural infection [27]. However, both peptidases stimulated detectable levels of TSLP from EC cells in vitro that suggests a role for this master cytokine of type 2 immune responses [28, 29] in initiating protective responses. Our previous studies have shown that delivery of TSLP to mice induced type-2 related protective immune responses against S .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that delivery of TSLP to mice induced type-2 related protective immune responses against S . mansoni challenge infection [11], which could have involved the recruitment and activation of eosinophils, basophils, and mast cells [2936]. …”
Section: Discussionmentioning
confidence: 99%
“…TSLP receptor is preferentially expressed on dividing human T H 2 cells isolated from allergic subjects 53 and on skin-homing T H 2 cells (CLA + CCR4 + CXCR3 − ) in patients with AD. 54 Moreover, skin-homing T cells increase their expression of TSLP receptor in response to IL-4 and enhance their secretion of IL-4 in response to TSLP, forming a positive feed-forward loop. T H 2 cells also positively feedback on epithelial cells in the allergic host to enhance their production of TSLP.…”
Section: Tslpmentioning
confidence: 99%